Triglyceride to high‐density lipoprotein cholesterol ratio is associated with incident diabetes in men: A retrospective study of Chinese individuals. Issue 1 (1st July 2019) - Qin, Hailun; Chen, Zekai; Zhang, Yunzhang; Wang, Lingyu; Ouyang, Piao; Cheng, Lan; Zhang, Yonggang
Abstract: Aims/Introduction: Dyslipidemia is commonly present in type 2 diabetes mellitus patients. Recently, the triglyceride : high‐density lipoprotein cholesterol (TG/HDL‐C) ratio, a novel parameter of lipid abnormality, has been seen as an independent predictor for incident diabetes. However, the correlation of the TG/HDL‐C ratio with incident diabetes in the Chinese population and how this relationship is impacted by sex have been rarely studied. In the present study, the correlation of the TG/HDL‐C ratio with incident diabetes is investigated between different sexes of the Chinese population. Materials and Methods: A total of 116, 855 participants who were free of diabetes at baseline were enrolled in the study. The participants were grouped by the median value (0.82) of the TG/HDL‐C ratio. Then, participants were further analyzed according to their sex. Cumulative incidence and person‐years incidence were used to express the incidence rate. The predictive value of the TG/HDL‐C ratio for incident diabetes was probed by the Cox regression proportional hazards model. Results: The mean age of the participants was 44.1 ± 12.9 years, and 53% of participants ( n = 62, 868) were the men. A total of 2, 685 incident diabetes cases occurred during the 3.1 years of the median follow‐up period. The cumulative incidence in total incident diabetes patients, men and women was 2.30% (2.21–2.38%), 3.01% (2.87–3.14%) and 1.47% (1.37–1.57%), respectively. After the adjustment of multivariate factors, the multivariate Cox regression analysis results showed that a higher TG/HDL‐C ratio was the independent predictive factor of incident diabetes in men (hazard ratio 1.30, 95% confidence interval 1.03–1.64), compared with women (hazard ratio 0.85, 95% confidence interval 0.53–1.38). Conclusions: Among the Chinese population, the TG/HDL‐C ratio is an independent predictor for incident diabetes in male patients. Abstract : This is the first large retrospective cohort study regarding the association of the triglyceride : high‐density lipoprotein cholesterol ratio with incident diabetes among Chinese. Among the Chinese population, elevated triglyceride : high‐density lipoprotein cholesterol ratio is independently and positively associated with the increased risk of incident diabetes in men.